Wind load evaluation on storm shelters using wind tunnel testing and North American design codes. (1st March 2022) - Ghazal, Tarek; Elshaer, Ahmed; Aboshosha, Haitham
Highlights: Three commonly used storm shelters have been experimentally tested for wind load. Wind tunnel was used to evaluate wind loads for structural system and cladding. Experimental results were compared to North American design codes. Potential modifications to account for the storm shelter's design were highlighted. Abstract: In Canada, the number of extreme wind events is increasing due to climate change. Accordingly, storm shelters are becoming more popular, as it provides a life-saving solution during wind events. Currently, the National Building code of Canada (NBCC 2015) and the American Society of Civil Engineers (ASCE 7-16) codes consider storm shelters as low-rise buildings with high importance factor with no specific guidelines for their smaller scale. The current study aims at comparing North American codes for designing wind shelters to a detailed experimental wind simulation using boundary layer wind tunnel testing under the synoptic wind. Wind tunnel tests were conducted at Ryerson University for three commonly used shapes of storm shelters. The governing wind loads from the wind tunnel results were compared to the design codes for both structural forces and cladding pressures. The study also illustrates and quantifies critical zones that may exceed the codes provided values due to being flow separation regions.